Ship construction - Eyres, David J. (Butterworth-Heinemann, 2007)
Ship Construction is a comprehensive text for students of naval architecture, ship building and construction, and for professional Naval Architects and Marine Engineers as a refresher on the latest developments in ship types, safety and shipyard practices. Beginning with an introduction to ship building and concluding with the finished product, the book enables the reader to follow the construction of a ship from start to finish. Eyres explores in depth, chapter by chapter, the development of ship types, materials and strengths of ships, welding and cutting, shipyard practice, ship structure and outfitting. The new edition includes a new chapter on computer-aided design and manufacture, and all the latest international regulations and technological developments. Covers the complete ship construction process including the development of ship types, materials and strengths of ships, welding and cutting, shipyard practice, ship structure and outfitting All the latest developments in technology and shipyard methods, including a new chapter on computer-aided design and manufacture Essential for students and professionals, particularly those working in shipyards, supervising ship construction, conversion and maintenance.